1998
DOI: 10.1017/s002211209800216x
|View full text |Cite
|
Sign up to set email alerts
|

Direct simulation of transition in an oscillatory boundary layer

Abstract: Numerical simulations of Navier–Stokes equations are performed to study the flow originated by an oscillating pressure gradient close to a wall characterized by small imperfections. The scenario of transition from the laminar to the turbulent regime is investigated and the results are interpreted in the light of existing analytical theories. The ‘disturbed-laminar’ and the ‘intermittently turbulent’ regimes detected experimentally are reproduced by the present simulations. Moreover it is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
138
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 18 publications
21
138
4
Order By: Relevance
“…Other workers have suggested that as the walls of a channel or pipe are not perfectly smooth some small roughness may be sufficient to prematurely trip disturbance modes at values of R far below the values suggested by the calculations. Blondeaux & Vittori (1994), Verzicco & Vittori (1996) and Vittori & Verzicco (1998) have shown that roughness on the walls of experimental apparatus can expediate the development of turbulence in this unsteady flow.…”
Section: Introductionmentioning
confidence: 95%
“…Other workers have suggested that as the walls of a channel or pipe are not perfectly smooth some small roughness may be sufficient to prematurely trip disturbance modes at values of R far below the values suggested by the calculations. Blondeaux & Vittori (1994), Verzicco & Vittori (1996) and Vittori & Verzicco (1998) have shown that roughness on the walls of experimental apparatus can expediate the development of turbulence in this unsteady flow.…”
Section: Introductionmentioning
confidence: 95%
“…Transition to turbulence has been investigated by direct numerical simulations of the Stokes boundary layer by Vittori & Verzicco (1998), Costamagna et al (2003) and Ozdemir et al (2014). Tuzi & Blondeaux (2008) have addressed the intermittent turbulent regime observed in a pulsating pipe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the idealised analytical flow has quite different stability properties from those seen in practice. For example, the perturbation growth can be amplified by wall roughness (Blondeaux & Vittori 1994;Vittori & Verzicco 1998) or a base flow variation (Thomas et al 2015).…”
Section: Introductionmentioning
confidence: 99%